Análisis de la degradación térmica en el proceso de pirólisis y la cinética asociada de madera de Ceiba aesculifolia (Kunth) Britt. & Baker - Méndez Zetina, Fernando Daniel (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The global energy landscape is currently undergoing a transition aimed at reducing dependence on fossil fuels, which, despite their dominance, are significant contributors to climate change. This shift underscores the importance of thermal degradation of Ceiba aesculifolia for the production of higher-value chemical products such as coke, oil, and gas. In this study, the thermogravimetric process (TGA-DTG) of C. aesculifolia was kinetically analyzed through thermal degradation in an inert nitrogen atmosphere, with temperatures ranging from 25 to 900 °C and varying heating rates (β = 10, 15, 20, 25, 30 °C/min). Activation energy and frequency factor were determined using different mathematical models, yielding the following results: Friedman (132.03 kJ/mol, 8.11 × 10¹⁰ s⁻¹), FWO (121.65 kJ/mol, 4.30 × 10⁹ s⁻¹), KAS (118.14 kJ/mol, 2.41 × 10⁹ s⁻¹), and Kissinger (155.85 kJ/mol, 3.47 × 10¹¹ s⁻¹). The reaction order, n (0.3937–0.6141), was calculated using the Avrami model. Thermodynamic parameters (ΔH, ΔG, ΔS) for each kinetic model were also evaluated. The results for Ea, A, ΔH, ΔG, and ΔS indicate that C. aesculifolia has considerable potential for use in pyrolysis processes. The chemical composition of C. aesculifolia consists of 77.7% holocellulose, 66.2% cellulose, 11.49% hemicellulose, 10.82% lignin, and 11.37% extractives. Proximate analysis revealed 9.37% moisture, 83.83% volatile matter, 14.33% fixed carbon, 1.84% low-molecular-weight inorganic components, and an energy content of 19.12 MJ/kg. Despite the ash content exceeding the limits established by international standards, this species can still be utilized as a local solid biofuel due to its high calorific value. Finally, Fourier-transform infrared spectroscopy (FT-IR) identified several key functional groups involved in the pyrolysis process, including aliphatic hydrocarbons.

Actualmente, el panorama energético global está dando un enfoque hacia la disminución del empleo de fuentes fósiles de energía, que predominan actualmente y son las principales responsables de las alteraciones climáticas en la actualidad, destacando así la relevancia de la degradación térmica de Ceiba aesculifolia con fines de conversión de productos químicos con un valor añadido mayor, como coque, aceite y gas. Este estudio presenta un análisis cinético del proceso termogravimétrico (TGA-DTG) de C. aesculifolia a través del proceso de degradación térmica, realizado en un rango de 25 a 900 °C en un espacio inerte (N₂) con diferentes tasas de calentamiento (β = 10, 15, 20, 25, 30 °C/min). Se calcularon la cinética de de arranque y el factor de colisiones utilizando diversos enfoques matemáticos, obteniendo los siguientes valores específicos: Friedman (132.03 kJ/mol, 8.11 × 10¹⁰ s⁻¹), FWO (121.65 kJ/mol, 4.30 × 10⁹ s⁻¹), KAS (118.14 kJ/mol, 2.41 × 10⁹ s⁻¹) y Kissinger (155.85 kJ/mol, 3.47 × 10¹¹ s⁻¹). La variación en el orden de reacción, n (0,3937–0,6141), se obtuvo mediante la teoría de Avrami. También se evaluaron los parámetros termodinámicos (ΔH, ΔG, ΔS) asociados a cada modelo cinético. Los resultados de Ea, A, ΔH, ΔG y ΔS sugieren que esta biomasa tiene un gran potencial para su utilización en procesos de pirólisis. La composición química de C. aesculifolia incluye 77.7% de holocelulosa, 66.2% de celulosa, 11.49% de hemicelulosa, 10.82% de lignina y 11.37% de extractivos. El análisis proximal mostró 9.37% de humedad, 83.83% de material volátil, 14.33% de carbono residual, 1.84% de componentes inorgánicos de bajo peso molecular y un potencial energético de 19.12 MJ/kg. Aunque el porcentaje de cenizas excede los límites permitidos por las normas internacionales, esta especie puede ser utilizada como biocombustible sólido a nivel local, dado el alto poder calorífico que presentó.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2024-1792; Pirólisis; Análisis cinético; Latifoliadas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18953